Pengaruh Model Pembelajaran The Power of Two terhadap Hasil Belajar IPS Peserta Didik - Febrianti, Aurora Nandia; Suryati, Wawat (STKIP PGRI Bandar Lampung, 2023)
The problems in this study were based on the not optimal learning situation that was implemented and resulted in low social studies learning outcomes for students. This study aims to determine the effect of applying The Power Of Two learning model on social studies learning outcomes for students in class VIII even semester at SMP Negeri 4 Terbanggi Besar Central Lampung in the 2022/2023 academic year. This study uses a quantitative approach to the type of research is experimental research. The population in this study were all students in class VIII consisting of 7 classes with a total of 202. The research sample was selected using a purposive random sampling technique by selecting class VIII F as the experimental class and class VIII G as the control class, where the experimental class used The Power model. Of Two and control classes use conventional learning methods. Data collection technique is done by testing technique. Furthermore, the data were analyzed using the t-test. From the research results, it can be concluded that the average social studies learning outcomes of students in the experimental class was 74.23 and the average learning outcomes in the control class were 69.45. From the calculation, we get thit = 4.01 by taking the 5% tdaf level = 1.69. Because thit > tdaf, it can be concluded that Ho was rejected, so the learning model of The Power of Two had an effect on social studies learning outcomes for class VIII students at SMP Negeri 4 Terbanggi Besar, Central Lampung.